2011
DOI: 10.1002/jbm.a.33299
|View full text |Cite
|
Sign up to set email alerts
|

Coating and release of an anti‐inflammatory hormone from PLGA microspheres for tissue engineering

Abstract: Many biomaterials used in tissue engineering cause a foreign body response in vivo, which left untreated can severely reduce the effectiveness of tissue regeneration. In this study, an anti-inflammatory hormone α-melanocyte stimulating hormone (α-MSH) was physically adsorbed to the surface of biodegradable poly (lactic-co-glycolic) acid (PLGA) microspheres to reduce inflammatory responses to this material. The stability and adsorption isotherm of peptide binding were characterized. The peptide secondary struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Recent studies by the O'Connor group have physically adsorbed α-MSH onto PLGA microspheres, which resulted in decreased TNFα production by LPS-activated RAW 264.7 macrophages at 24 and 48 h but not 72 h compared to control surfaces [73]. There was not a strong effect of the adsorbed α-MSH when implanted subcutaneously into the backs of rats.…”
Section: Delivering Molecules To Control Macrophage Polarizationmentioning
confidence: 99%
“…Recent studies by the O'Connor group have physically adsorbed α-MSH onto PLGA microspheres, which resulted in decreased TNFα production by LPS-activated RAW 264.7 macrophages at 24 and 48 h but not 72 h compared to control surfaces [73]. There was not a strong effect of the adsorbed α-MSH when implanted subcutaneously into the backs of rats.…”
Section: Delivering Molecules To Control Macrophage Polarizationmentioning
confidence: 99%
“…29,38 A multilayer film constructed on top of the a-MSH is expected to act as a barrier to the release of a-MSH, slowing diffusion from the porous microspheres. The polyelectrolyte concentration required to produce a uniform coating on the surface and within the pores of the microspheres during multilayer assembly was first investigated using confocal microscopy ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…24 We have also shown that a 13 amino acid antiinflammatory hormone, alpha melanocyte stimulating hormone (a-MSH), could be directly incorporated as the base building block in a multilayer film on PLGA, due to strong binding to the PLGA surface. 29 Here we demonstrate that these approaches can be combined to form a single tunable multilayer delivery system to release both these bioactive molecules at biologically relevant concentrations. Porous PLGA microspheres are introduced to provide a biodegradable support that facilitates efficient multilayer formation and biomolecule delivery with much higher loading capacity than nonporous spheres.…”
Section: 28mentioning
confidence: 98%
“…These molecules target different receptor pathways in the inflammation cascade and can thus be interesting alternatives or complements to the Dex (Bridges and Garcia, 2008; Go et al, 2012). All of the listed molecules are typically delivered from passively eluting systems due to their chemical properties and overall size, which makes them incompatible with the ion-exchange principle provided by conducting polymers.…”
Section: Discussionmentioning
confidence: 99%